Growth and development of Alphitobius diaperinus (Panzer)(Coleoptera: Tenebrionidae) developing from pupae irradiated with ultra-violet rays (University Journal of Zoology, Rajshahi University, 2007)
Key words: UV-rays; Alphitobius diaperinus; growth developmental periods Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 23-26